The pentothal test in the management of orthopaedic patients with hysterical illness. - Cornell, M S (1996)
Hysterical illness may be defined as symptoms normally associated with disease without pathological basis. Orthopaedics attracts more of these patients than most specialties. They are intensively and expensively investigated, yet clinicians remain anxious they are missing genuine pathology. We use examination under pentothal, without analgesia, to help distinguish real from imagined symptoms. The results of a review of patients evaluated under pentothal over the past two years are presented.